2018
DOI: 10.1161/circulationaha.117.030469
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Soluble ST2 as a Novel Biomarker for Acute Aortic Dissection

Abstract: Among patients with suspected aortic dissection in the emergency department, sST2 showed superior overall diagnostic performance to D-dimer or cardiac troponin I. Additional study is needed to determine whether sST2 might be a useful rule-out marker for AAD in the emergency room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 38 publications
3
78
1
2
Order By: Relevance
“…The present study post-dated the study by Wang et al reporting high sensitivity and specificity of plasma sST2 for AASs and indicating potential superiority of sST2 to D-dimer 21 . Several issues may cause the discrepancy between current and previous data.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The present study post-dated the study by Wang et al reporting high sensitivity and specificity of plasma sST2 for AASs and indicating potential superiority of sST2 to D-dimer 21 . Several issues may cause the discrepancy between current and previous data.…”
Section: Discussionsupporting
confidence: 83%
“…The role of sST2 within vascular tissues and in the context of aortic disease is largely unknown 20 . However, Wang et al recently reported that plasma sST2, measured with a research-grade assay, showed striking diagnostic accuracy for AASs and outperformed D-dimer, in a Chinese patient cohort 21 . Since plasma sST2 levels can be measured with a clinical-grade assay already approved for patient use, we sought to further evaluate it as a diagnostic biomarker for AASs in an independent prospective cohort of acute patients from a European ED.…”
mentioning
confidence: 98%
“…Venous blood was immediately sent to the clinical laboratory center of the Anzhen hospital. Plasma PT, APTT, FDP, and D-dimer were measured using the commercially available automated latex immunoturbidimetric assay (Werfen ACL TOP 700, United States) (Di Nisio et al, 2007;Wang et al, 2018). Routine blood tests and some biochemical indicators were determined by standard quantitative assay techniques, according to the manufacturers' instructions.…”
Section: D-dimer Measurementmentioning
confidence: 99%
“…Previous studies have reported that sST2 can be used as a prognostic biomarker for the development of systemic and highly inflammatory diseases, such as aortic dissection, sepsis, and heart failure as well as mortality in patients with these diseases. [36][37][38] This hypothesis is reinforced by the finding that plasma sST2 concentrations could predict poor prognosis in patients with acute-on-chronic hepatitis B liver failure. 39 The present study further revealed its prognostic .…”
Section: Discussionmentioning
confidence: 99%